The Integration of Karl Popper’s Falsification Theory in the Reconstruction of Modern Islamic Educational Epistemology - Afriyanto, Dwi; Suwardi, Suwardi; Mubarok, Imam (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This study explores the integration of Karl Popper's falsification theory in the reconstruction of the epistemology of modern Islamic education as a methodological strategy to respond to dogmatic tendencies and stagnation in the development of Islamic scientific discourse. With a qualitative approach based on literature studies, this study confirms that falsification functions as an evaluative instrument that allows for critical and contextual re-examination of the validity of Islamic theories. The main findings show that the application of falsification encourages a more adaptive curriculum reformulation to social dynamics and scientific progress, while facilitating the creation of a dialogical learning space, where students play an active role as subjects seeking truth. This principle also strengthens the integration between rationality and revelation through an epistemological framework based on ijtihad and tajdid. Thus, falsification not only provides a methodological contribution to the development of science but also presents a solid philosophical foundation for the development of an Islamic education system that is reflective, progressive, and open to scientific innovation, without neglecting the transcendental values ​​that are its characteristics. The primary limitation of this study lies in its conceptual-theoretical nature, necessitating empirical field research to validate this epistemological model within tangible Islamic educational institutions